2019
DOI: 10.1210/js.2019-00096
|View full text |Cite
|
Sign up to set email alerts
|

Cardiometabolic Effects of Endocrine Treatment of Estrogen Receptor–Positive Early Breast Cancer

Abstract: Estrogen receptor–positive early breast cancer is common and has a relatively good prognosis. It shares risk factors with cardiovascular disease, and cardiovascular disease is an important competing cause of mortality. Adjuvant endocrine therapy with aromatase inhibitors (requiring concomitant ovarian suppression in premenopausal women) or selective estrogen receptor modulators (usually tamoxifen) exert oncologic benefits by respectively inhibiting estradiol synthesis or breast estrogen receptor signaling. Aro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 104 publications
(124 reference statements)
0
17
1
1
Order By: Relevance
“…In addition to previous treatments, the current therapy with AIs may lead to increased cardiovascular risk [ 12 ]. As mentioned, this may occur due to a reduction in the levels of estrogen, a hormone associated with cardiovascular protection [ 13 ]. It is worth mentioning that, despite this, such treatments are extremely important for women diagnosed with BC [ 8 ] and should not be discouraged.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to previous treatments, the current therapy with AIs may lead to increased cardiovascular risk [ 12 ]. As mentioned, this may occur due to a reduction in the levels of estrogen, a hormone associated with cardiovascular protection [ 13 ]. It is worth mentioning that, despite this, such treatments are extremely important for women diagnosed with BC [ 8 ] and should not be discouraged.…”
Section: Discussionmentioning
confidence: 99%
“…Among the drugs used in this treatment, aromatase inhibitors (AIs) have high efficacy in women in the postmenopausal stage [ 10 , 11 ], however, they are associated with increased risk of vascular disease, myocardial infarction and angina [ 12 ]. One possible explanation is that the drug reduces estrogen levels, and these hormones are related to cardiovascular protection [ 13 ]. A prospective study has shown that 80% of women with prescriptions for this therapy have a predicted risk of CVDs in ten years equal to or higher than the risk of recurrence of BC [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the available evidence suggests that neither tamoxifen nor aromatase inhibitors are associated with increased cardiovascular events. 55 More detailed evidence is needed in this cohort to better guide the management of cardiovascular risk in women after breast cancer.…”
Section: Menopause-associated Cardiovascular Riskmentioning
confidence: 99%
“…64 Recent reports by Suzuki et al and others suggest that patients with atherosclerotic plaques could be at a higher risk for developing cancer. 19,32,103 Other reports indicate that long-term cardiovascular risk attenuates cancer survival rate and efficacy of early cancer therapy, particularly with respect to breast cancer, which has been the cancer of focus in our research laboratory. 36,53 Furthermore, it is known that cardiovascular disease contributes to a majority of the deaths amongst breast cancer patients.…”
Section: Introduction: Why Study Glycocalyx-mediated Intercellular Inmentioning
confidence: 99%